2008
DOI: 10.1039/b712298e
|View full text |Cite
|
Sign up to set email alerts
|

The quest for secondary structure in chiral dendrimers

Abstract: This review highlights important developments in the pursuit of chiral conformational order in dendritic structures. To be able to create and control chiral secondary structure necessitates a thorough understanding of how chiral subunits influence the macroscopic structure. Recent studies involve highly sophisticated manipulation of macroscopic chirality through a creative combination of a wide range of synthetic, computational and analytical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…31 The resulting material, which featured a unique chiral nanotube motif, anionic nanotunnels, was proposed by the authors for exploring sorption, inclusion and for applications in enantioselective separation and catalysis. 31 Expanding to a broader area of chirality at the nanoscale, excellent reviews on surface chirality, 32 chiral monolayers, 33 and chirality in dendrimers 34 have been published very recently, as strong indicators of a rapidly increasing interest in this field. Summarizing the recent progress relevant to chiral nanoblocks, a new chiral zeolite family has been recently reported for silicogermanates.…”
Section: Vladimir Kitaevmentioning
confidence: 99%
“…31 The resulting material, which featured a unique chiral nanotube motif, anionic nanotunnels, was proposed by the authors for exploring sorption, inclusion and for applications in enantioselective separation and catalysis. 31 Expanding to a broader area of chirality at the nanoscale, excellent reviews on surface chirality, 32 chiral monolayers, 33 and chirality in dendrimers 34 have been published very recently, as strong indicators of a rapidly increasing interest in this field. Summarizing the recent progress relevant to chiral nanoblocks, a new chiral zeolite family has been recently reported for silicogermanates.…”
Section: Vladimir Kitaevmentioning
confidence: 99%
“…The bisignet nature of this absorption is due to the excitonic coupling of the π → π * transitions of the terminal anthranilate chromophores, which are polarized along the axis containing C3 and C6. The presence of the negative couplet indicates that both 4a and 5a adopt an Mtype helical conformation relating the anthranilate chromophores in CH 3 CN (Parquette 2003;Lockman et al 2005;Gibson & Rendell 2008). The spectra were normalized with respect to concentration and the total number of terminal groups to determine the extent of chiral amplification from the chiral ('sergeants') to the achiral termini ('soldiers').…”
Section: (B) Conformational Properties: Circular Dichroismmentioning
confidence: 99%
“…Although 'sergeants and soldiers' chiral amplification has been achieved in dendritic assemblies (Palmans et al 1997; van Gestel et al 2005;Wilson et al 2006;Shao & Parquette 2008;Percec et al 2009), an intramolecular 'sergeants and soldiers' type chiral amplification remains an unrealized objective for dendrimeric systems. However, recent progress towards the incorporation of chiral secondary structure provides an opportunity to explore such chiral amplification in dendrimers (Parquette 2003;Lockman et al 2005;Gibson & Rendell 2008). In a series of folded dendrimers, preorganized via the conformational preference of a pyridine-2,6-dicarboxamide repeat unit, we observed that coupled motions within the branches were critical for the amplification of chirality throughout the dendrons (Recker et al 2000;Huang & Parquette 2001;Parquette 2003;Lockman et al 2005) Recently, the propagation/amplification of local chirality within catalysts derived from these folded dendrons was successfully exploited to achieve high enantioselectivity in a catalytic process (Yu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This allowed the development of the kinetic model proposed in this work. For this proposal, a layer-by-layer assembled was formed by the adsorption on gold surface of cysteamine followed by the addition of a fourth-generation poly(amidoamine) dendrimer (PA-MAM(G4)) for the immobilisation of this C1 antigen (Gibson et al, 2008;Mark et al 2004). In addition, with the use of a proposed model based on bivalent ligation, it was possible to demonstrate the reaction kinetic and the binding affinity between the C1 antigen and the specific anti-L. infantum antibodies.…”
Section: Introductionmentioning
confidence: 99%